Rare clinical presentations and advances in the treatment of Buerger’s disease - narrative review - Chruścicki, Damian; Bednarczyk, Paulina; Kulej, Wojciech; Płonka, Wojciech; Pelc, Marcin; Sitarek, Gracjan; Żerek, Marta; Waszczyński, Jakub (Quality in Sport, 2024)
Introduction Buerger’s disease (BD) is an inflammatory disease with an etiology that is still not fully understood. It involves venous and arterial vessels, of small and medium caliber, of the lower and upper extremities (Cacione et al., 2020). This inflammation predominantly affects young, tobacco-smoking men, usually those before the age of 40. Literature data relating to peripheral arterial disease in general, put the prevalence of BD at between 0.5%-5.6% in Western European countries (Liu et al., 2023; Öztan et al., 2023). In this paper, we summarized the latest literature reports on rare clinical images and new directions in the treatment of Buerger’s disease. Aim of the study The purpose of this systematic review was to compile the latest literature on the etiology, atypical disease presentation, associations with other diseases and modern treatment of Buerger’s disease. Materials and methods The materials used by our team were obtained from a review of the currently available literature in the PubMed database. To search for articles, we used keywords such as: Buerger’s disease, thromboangiitis obliterans, thrombosis, atherosclerosis, Peripheral arterial disease, vasculitis. Conclusion In addition to its characteristic clinical presentation, Buerger’s disease can present under a number of atypical forms. Such examples, less common conditions in the course of BD are intestinal vascular involvement mimicking the condition of acute abdomen, infertility condition due to gonadal involvement in the patient, possible correlation between the level of ASA (anti-sperm antibodies) and reduced fertility, the occurrence of nail lesions, renal complications, including the nephrotic syndrome, ocular or psychiatric manifestations. It is important for the clinician, in the diagnostic and therapeutic process at the onset of the described symptoms, not to exclude the possibility of an uncommon course of BD, to make a correct diagnosis and undertake optimal treatment.